Dynamic Effects of Shadow Economy and Environmental Pollution on the Energy Stock Prices - Şenhaz, Zehra (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This thesis aims to study the dynamic effects of shadow economies and environmental pollution on energy stock prices by empirically investigating the case of Turkey and the Organization for Economic Co-operation and Development (OECD) countries using Generalized Methods of Moments (GMM). The GMM analysis of Turkey has been done years from 2006 to 2014. The results of GMM analysis show that; negative link exists between shadow economies and the energy stock prices of Turkey. Therefore, an increase in shadow economies decreases the energy stock prices. Additionally, energy stock performance is not significantly related to environmental deterioration. Nevertheless, it is also found that the level of shadow economies rises with growth in energy consumption and emission levels. The analysis of OECD countries covers years from 2004 to 2014. The results of GMM analysis show a significant relationship exists between shadow economies, energy stock prices, and environmental pollution. Environmental pollution negatively affects energy stock prices even energy demand found positively linked with energy stock prices. On the other hand, U- shaped relationship found between energy stock prices and shadow economies, which means the response of energy stock prices to the volume of shadow economies is negative at the lower level of shadow economies; then beyond a trough point, this link turns to be positive with the higher level of shadow economies. Keywords: energy stock prices, shadow economies, environmental pollution, generalized methods of moments, Turkey, OECD.

ÖZ: Bu tezin amacı çevre kirliliği ve kayıt dışı ekonominin enerji hisse senedi fiyatları üzerindeki dinamik etkilerini araştırmaktır. Bu konu üzerinde Genelleştirilmiş Momentler Yöntemi (GMM) kullanılarak Türkiye ve Ekonomik Kalkınma ve İşbirliği Örgütü (OECD) ülkeleri ile çalışılmıştır. Çalışmada Türkiye için 2006 yılından 2014 yılına kadar olan yıllık dönem ele alınmıştır. Yapılan GMM analizleri sonucunda kayıt dışı ekonomiyle enerji hisse senedi fiyatları arasında negatif yönlü bir ilişki tespit edilmiştir. Böylelikle, kayıt dışı ekonominin hacmindeki artış enerji hisse senedi fiyatlarını düşürdüğü ortaya konulmuştur. Buna ek olarak, enerji hisse senedi fiyatları ve çevre kirliliği arasında bir ilişki saptanamamasına rağmen, enerji talebi ve karbon emisyonundaki artışın, kayıt dışı ekonomiyi artırdığı saptanmıştır. OECD ülkeleri için 2004 yılından 2014 yılına kadar olan yıllık dönem ele alınmıştır. Elde edilen sonuçlar kayıt dışı ekonomi, enerji hisse senedi fiyatları ve çevre kirliliği arasında önemli bir ilişki olduğunu ortaya koymaktadır. Çevre kirliliğinin enerji hisse senedi fiyatlarını olumsuz etkilediği görülmesine rağmen, enerji talebindeki artışın enerji hisse senedi fiyatlarını artırdığı gözlemlenmiştir. Kayıt dışı ekonomi ile enerji hisse senedi fiyatları arasında U- şeklinde bir ilişki olduğu bulunmuş ve bu ilişki kayıt dışı ekonominin ilk aşamalarında enerji hisse senedi fiyatlarıyla negatif yönlü, dip noktasına eriştikten sonraysa pozitif yönlü olduğu şeklinde açıklanabilmektedir. Anahtar Kelimeler: enerji hisse senedi fiyatları, kayıt dışı ekonomi, çevre kirliliği, genelleştirilmiş momentler yöntemi, Türkiye, OECD.
Doctor of Philosophy in Finance. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Prof. Dr. Salih Katırcıoğlu.
Keywords: Banking and Finance; Informal sector (Economics); Energy Economics; Energy stock prices; shadow economies; environmental pollution; generalized methods of moments; Turkey; OECD